Analysis of the efficiency and effectiveness of the budget for the DPR's aspirational funds in Mimika Regency - Nasrum, Nasrum; Iek, Mesak; Ngutra, Risky Novan (Goodwood Publishing, 2024)
Purpose: This study aims to evaluate the efficiency and effectiveness of the DPRD’s aspirational funds (Pokok Pikiran) in Mimika Regency, focusing on their impact on public welfare and alignment with regional development priorities. Research/methodology: A descriptive quantitative approach was used, with primary data collected through questionnaires and interviews with community members and stakeholders in the DPRD and local government. Secondary data included budget realization reports from 2022–2024. Effectiveness and efficiency were measured using ratio analysis. Results: The average effectiveness reached 95.3%, showing that most allocated funds were realized. However, efficiency declined, with the Pokok Pikiran share in direct spending dropping from 5.6% in 2022 to 2.89% in 2024, despite growing regional expenditure. Several programs, such as housing development, had limited welfare impact, suggesting poor alignment with strategic needs. Conclusions: While the funds were effectively utilized, their efficiency in enhancing public welfare was limited due to weak program impact and misaligned priorities. Strategic planning and targeting are necessary to improve outcomes. Limitations: The study is limited to one region and a short timeframe (three years), without comprehensive input from beneficiaries, limiting the assessment of long-term impacts. Contribution: This study offers empirical insights into DPRD fund management, identifying the gap between budget realization and public benefit. It informs policy improvements in fund prioritization, transparency, and welfare impact in decentralized governance.